2016
DOI: 10.1016/j.dnarep.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Roles for mismatch repair family proteins in promoting meiotic crossing over

Abstract: The mismatch repair (MMR) family complexes Msh4-Msh5 and Mlh1-Mlh3 act with Exo1 and Sgs1-Top3-Rmi1 in a meiotic double strand break repair pathway that results in the asymmetric cleavage of double Holliday junctions (dHJ) to form crossovers. This review discusses how meiotic roles for Msh4-Msh5 and Mlh1-Mlh3 do not fit paradigms established for post-replicative MMR. We also outline models used to explain how these factors promote the formation of meiotic crossovers required for the accurate segregation of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
112
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 168 publications
(185 reference statements)
3
112
0
1
Order By: Relevance
“…It is possible that MCMDC2 participates in promoting MSH4/5 function or other members of the ZMM complex that stabilize D-loops formed by invasion of single-stranded ends into homologous sequences (Manhart and Alani 2016). Such a scenario would link to the hypothesis that the Mei-MCM complex in Drosophila adapted to serve the function(s) of MSH4/5 (Kohl et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that MCMDC2 participates in promoting MSH4/5 function or other members of the ZMM complex that stabilize D-loops formed by invasion of single-stranded ends into homologous sequences (Manhart and Alani 2016). Such a scenario would link to the hypothesis that the Mei-MCM complex in Drosophila adapted to serve the function(s) of MSH4/5 (Kohl et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms regulating CO vs. NCO recombination is an area of intense study. Most of the CO events in both yeast and mice require proteins of the ZMM complex, including MSH4 and MSH5, which stabilize recombination intermediates and facilitate double Holliday junction formation after initial D-loops are formed by invasion of a singlestranded end of a resected DSB (Manhart and Alani 2016). In part, this is done by inhibiting the anti-CO activity of BLM helicase, which otherwise promotes synthesis-dependent strand annealing and NCO repair (Jessop et al 2006;Oh et al 2007;Holloway et al 2010;De Muyt et al 2012).…”
mentioning
confidence: 99%
“…MutLα (Mlh1-Pms1) is the primary endonuclease complex functioning in the MMR pathway, and MutLγ (Mlh1-Mlh3) plays only a minor role (58,59). In contrast, MutLγ has a major role in meiotic recombination during Holiday junction (HJ) resolution (60). Indeed, in vitro studies showed that MutLγ can bind to HJs and other heteroduplex structures independently of Msh2, although loading of the Msh2/ Msh3 complex enhanced MutLγ nicking of supercoiled DNA (43,61).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these promote genome stability, such as suppression of homeologous recombination (by disrupting exchange between heteroduplex DNA substrates) [12,92], while others promote genome instability, such as expansion of triplet nucleotide repeat (TNR) sequences [93], processing of DNA oxidative damage lesions [94], and somatic hypermutation for antibody diversity [95]. For example, Msh2-Msh3 (MutSβ), which binds and initiates repair of insertion/deletion loops (post-replication or during recombination), also binds double strand/single strand junctions (for removal of 3’non-homologous tails in double strand break repair) [96], as well as secondary structures formed by repeat sequences (leading to TNR expansion and related neurological disorders) [97].…”
Section: Ongoing Research On How Atpase-coupled Actions Of Muts Anmentioning
confidence: 99%